2003
DOI: 10.1074/jbc.m302946200
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the Matricellular Protein SPARC by Matrix Metalloproteinase 3 Produces Polypeptides That Influence Angiogenesis

Abstract: SPARC, a matricellular protein that affects cellular adhesion and proliferation, is produced in remodeling tissue and in pathologies involving fibrosis and angiogenesis. In this study we have asked whether peptides generated from cleavage of SPARC in the extracellular milieu can regulate angiogenesis. Matrix metalloproteinase (MMP)-3, but not MMP-1 or 9, showed significant activity toward SPARC. Limited digestion of recombinant human (rhu)SPARC with purified catalytic domain of rhuMMP-3 produced three major fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
111
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 55 publications
(55 reference statements)
1
111
0
5
Order By: Relevance
“…It has been noted that simply adding exogenous copper to a cell system can initiate angiogenesis (6); translocation of intracellular copper to the extracellular space as demonstrated here may be serving the same purpose. Alternatively, peptides resulting from the proteolytic degradation of extracellular matrix proteins such as SPARC/osteonectin (33) may be activated by excreted copper and behave as proangiogenics in an autocrine manner (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that simply adding exogenous copper to a cell system can initiate angiogenesis (6); translocation of intracellular copper to the extracellular space as demonstrated here may be serving the same purpose. Alternatively, peptides resulting from the proteolytic degradation of extracellular matrix proteins such as SPARC/osteonectin (33) may be activated by excreted copper and behave as proangiogenics in an autocrine manner (34).…”
Section: Discussionmentioning
confidence: 99%
“…Intact SPARC inhibits the angiogenic response by impairing proper collagen alignment and blocking pro-angiogenic growth factors (Kupprion et al, 1998). At the same time it has been reported that cleaved SPARC might facilitate vessel growth by enhancing endothelial cell proliferation (Sage et al, 2003). In aged tissues, the complexities surrounding the role of SPARC in the angiogenic response are obviated by age-related deficits in the levels of growth factors and other pro-angiogenic mediators (Reed et al, 2005).…”
Section: Matricellular Proteinsmentioning
confidence: 99%
“…This is also suggested by the binding of VEGF by SPARC and reduced VEGF receptor activation in the presence of SPARC (11). However, it has been observed that cleavage of SPARC by matrix metalloproteinases and plasmin releases peptides that are pro-angiogenic (15,16). These peptides are found within the follistatin-like domain of SPARC (8,15).…”
mentioning
confidence: 96%